Leafy Greens in Hydroponics and Protected Culture for Florida - Natalie B. Parkell; Robert C. Hochmuth; Wanda L. Laughlin (EDIS, 2016)
Leafy greens are some of the top “powerhouse” fruits and vegetables. They are also becoming increasingly more popular for consumers. This 7-page fact sheet is designed to aid Florida hydroponic and/or other protected culture growers who are seeking appropriate cultivars of the leafy greens group. The article covers spinach, Swiss chard, kale, collard greens, mustard greens, and Asian greens. Written by Natalie B. Parkell, Robert C. Hochmuth, and Wanda L. Laughlin, and published by the Horticultural Sciences Department, April 2016.